Christian Spiritual Formation in the Classical School. Issue 2 (November 2018) - Miller, Matthew R.; Beazley, JohnMark Bennett
Classical Christian education has ancient roots in the Christian church. In recent days, Christians have attempted to recover this classical tradition. Many cite the intellectual rigor vis-à-vis public schools as the reason for choosing classical Christian education. However, intellectual rigor is only one part of the classical tradition. More importantly, classical Christian education seeks to develop morally upright Christians. This education forms the character of Christians so that they may live faithfully in the world. This article describes how classical Christian education works at Highlands Latin School in Louisville, KY. Specifically, the implementation of the classical curriculum in middle school Latin and Greek courses is addressed with an eye toward spiritual/moral formation.